An analysis of British university student anti-bullying policies: how British universities compare with Australian universities. Issue 1 (2nd January 2021) - Vaill, Zoe; Campbell, Marilyn; Whiteford, Chrystal
ABSTRACT: Policy is an important part of prevention and intervention when it comes to peer bullying amongst university students. Therefore, the contents of these policies need to be informative and easy to find, understand and use. With the United Kingdom having a low prevalence of peer bullying at university when compared to other countries, determining whether the quality of a university student anti-bullying policy is related to the prevalence, may help universities in other countries reduce bullying prevalence. This study adds to the body of knowledge by analysing the content and usability of student anti-bullying policies of 39 universities in the UK. The results were then compared to the results of a similar study conducted with Australian universities, to determine similarities and difference, and where improvements could be made. Through this, and future studies, it is hoped that a relationship can be determined between the quality of university student anti-bullying policies, and the prevalence of bullying. It is also hoped that the results of this study will allow universities to identify where their policy may be improved and promote the importance of having a bully-free culture on campus.